Intrarater reliability and agreement of linear encoder derived heel-rise endurance test outcome measures in healthy adults - Byrne, C; Keene, DJ; Lamb, SE; Willett, K (Elsevier, 2017)
A linear encoder measuring vertical displacement during the heel-rise endurance test (HRET) enables the assessment of work and maximum height in addition to the traditional repetitions measure. We aimed to compare the test-retest reliability and agreement of these three outcome measures. Thirty-eight healthy participants (20 females, 18 males) performed the HRET on two occasions separated by a minimum of seven days. Reliability was assessed by the intraclass correlation coefficient (ICC) and agreement by a range of measures including the standard error of measurement (SEM), coefficient of variation (CV), and 95% limits of agreement (LoA). Reliability for repetitions (ICC = 0.77 (0.66, 0.85)) was equivalent to work (ICC = 0.84 (95% CI 0.76, 0.89)) and maximum height (ICC = 0.85 (0.77, 0.90)). Agreement for repetitions (SEM = 6.7 (5.8, 7.9); CV = 13.9% (11.9, 16.8%); LoA = −1.9 ± 37.2%) was equivalent to work (SEM = 419 J (361, 499 J); CV = 13.1% (11.2, 15.8%); LoA = 0.1 ± 34.8%) with maximum height superior (SEM = 0.8 cm (0.6, 1.0 cm); CV = 6.6% (5.7, 7.9%); LoA = 1.3 ± 17.1%). Work and maximum height demonstrated acceptable reliability and agreement that was at least equivalent to the traditional repetitions measure.